Study of Liquid Self-nanoemulsifying Drug Delivery System (L-SNEDDS) that Use Oleic Acid as the Oil Phase: Literature Review - Lestari, Ratih Guswinda; Sukmawati, Anita (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Self-Nanoemulsifying Drug Delivery System (SNEDDS) is a nanoemulsion system that can be used to increase the bioavailability of drugs that are hardly soluble in water and have low bioavailability. Oleic acid, a saturated fatty acid that is found in many vegetable oils, is an oil that is often used for the oil phase in SNEDDS. Therefore, this review article aims to review, study, analyze and explore the optimum formula of SNEDDS that use oleic acid as the oil phase. The articles were searched via Google Schoolar, Science Direct, and Pubmed. The total number of articles is 464 articles. The total number articles that include exclusion criteria is 453 articles. The total article that use is 11 articles. SNEDDS, which uses oleic acid as the oil phase, produces droplet sizes of 19.75-190.03 nm with a polydispersity index of 0.278-0.532. Zeta potential value, only 2 articles have a zeta potential value above +/-30, that is mefenamic acid SNEDDS and furosemide SNEDDS. Overall, SNEDDS which uses oleic acid as the oil phase has a better dissolution and bioavailability profile compared to the commercial product or the pure drug. If solubility and bioavailability increase, it can increase the pharmacological activity of the drugs